EFISIENSI EKONOMI USAHATANI KUBIS ( DI KECAMATAN BUMIAJI, KABUPATEN MALANG) - Niniek Dyah Kusumawardani; Dwidjono Hadi Darwanto; Moch. Maksum (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2002)
The objectives of this study were to know : (1) the factors that affected income: and (2) the economic efficiency of cabbage farm. The study was conducted at Desa Tulungrejo, the main cabbage production area of Kecamatan Bumiaji, Kabupaten Malang. The method of sample selection was random with 88 respondent who planted cabbage on wet season 2000/2001 or dry season 2001. Some factors that affected the real income per hectare were the real price of seed, the real price of anorganic and organic fertilizer, the real price of liquid and non liquid pesticides, and the real wage of hired labor. The cabbage farms per hectares were not economically efficient.